Understanding plant resource use by the ≠Khomani Bushmen of the southern Kalahari - Mannetti, Lelani (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScConEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.